Avaliação da dor em crianças sob ventilação mecânica invasiva em unidade de terapia intensiva pediátrica - Dantas, Layra Viviane Rodrigues Pinto (2012)
Pain in children is still being inadequately addressed by health professionals, which can be due to difficulties for Pain evaluation in this population. In an intensive care environment and under mechanical ventilation, this difficulty tends to be increased due to small number of appropriate tools to measure pain in these individuals. Purpose. To measuere pain in sedated and mechanically ventilated pediatric patients in an intensive care unit. Methods. Thirty-five children participated in the search, being admitted to the pediatric intensive care unit at Sergipe Emergency Hospital (HUSE), aged between 1 month and 12 years old who were undergoing invasive mechanical ventilation and sedation. These children were evaluated in three times: before, during and five minutes after the painful procedure of arterial blood gas analysis. Pain assessment was performed using the FLACC scale, besides the measurement of physiological variables: heart rate, respiratory rate, oxygen saturation and blood pressure. Results: It was observed significant variation in FLACC (p=0,0001) scale among three moments, with an increase in their scores during painful stimulus. For the physiological variables, it was observed pain influence in heart rate (p=0,03), respiratory rate (p= 0,001) and diastolic blood pressure (p=0,006), whereas systolic blood pressure and oxygen saturation did not vary significantly among three moments. Conclusion. Mechanically ventilated and sedated children feel pain, once FLACC scores were increased and some physiological variables during noxious stimuli. This scale had adequate reliability for the population studied, so this study suggests to use the FLACC pain assessment in mechanically ventilated children.